2004
DOI: 10.1038/sj.bmt.1704675
|View full text |Cite
|
Sign up to set email alerts
|

Ex vivo expansion of megakaryocyte precursor cells in autologous stem cell transplantation for relapsed malignant lymphoma

Abstract: Summary:To evaluate the impact of ex vivo expanded megakaryocyte (MK) progenitors on high-dose chemotherapyinduced thrombocytopenia, we conducted a phase II study in 10 patients with relapsed lymphoma. Two fractions of peripheral blood progenitor cells (PBPC) were cryopreserved, one with enough cells for at least 2 Â 10 6 CD34 þ cells/kg and a second obtained after CD34 þ selection. Ten days before autologous stem cell transplantation, the CD34 þ fraction was cultured with MGDF þ SCF for 10 days. After BEAM (B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 19 publications
1
21
0
1
Order By: Relevance
“…Besides, in the clinical trials with ex vivo generated MKs published so far, only positive effects on neutrophil recovery and no negative effect on other blood cell lineages were observed. [1][2][3][4] Together, these data indicate that the addition of ex vivo generated MKs to the transplant does not influence the engraftment potential, engraftment pattern or the differentiation capacity of the unmanipulated CD34 þ cells in various mouse organs.…”
Section: Figurementioning
confidence: 98%
See 1 more Smart Citation
“…Besides, in the clinical trials with ex vivo generated MKs published so far, only positive effects on neutrophil recovery and no negative effect on other blood cell lineages were observed. [1][2][3][4] Together, these data indicate that the addition of ex vivo generated MKs to the transplant does not influence the engraftment potential, engraftment pattern or the differentiation capacity of the unmanipulated CD34 þ cells in various mouse organs.…”
Section: Figurementioning
confidence: 98%
“…Another clinical study with 10 lymphoma patients showed no positive effect of the addition of MKs, while higher CD61 þ cell numbers were infused. 2 In that study, however, cells were cultured for 10 days in the presence of MGDF and SCF. The longer culture period in this study might well have resulted in more mature, larger and thus possibly more fragile MKs, which might therefore show less efficient homing and platelet production in vivo.…”
Section: Figurementioning
confidence: 99%
“…As an alternative to PLT transfusion to treat thrombocytopenia, the transfusion of their precursors (MKs) has been proposed (22). Poncz et al have previously demonstrated the feasibility to increase PLT counts in the blood circulation upon MK transfusion.…”
Section: Hla-universal Mks Generate Plts In a Refractoriness Mouse Modelmentioning
confidence: 99%
“…However, in prior studies, the numbers of BM MKs collected were insufficient for a therapeutically effective transfusion (22,23). Transfusion of NOD/SCID/IL2Rγc -/-mice with either HLA-expressing or HLA-silenced iPSC-derived MKs resulted in the production of PLTs, which were detectable in the murine circulation.…”
Section: Hla-universal Mks Generate Plts In a Refractoriness Mouse Modelmentioning
confidence: 99%
“…Trombositlerin yaşam ömürleri oldukça kısa olduğundan, onların kan merkezlerinde uzun süre saklanması mümkün değildir ve bu nedenle trombositopeni tedavisi günü-müzde ciddi bir sorun olmaya devam etmektedir. Böy-le durumların tedavisi için standart protokoller dışında ex vivo olarak farklılaştırılmış megakaryosit-progenitör hücrelerin (MPH) hastalara verilmesi stratejisi üzerinde yoğun araştırmalar yapılmaktadır [1,2]. Çok kısa sürede vücutta trombosite dönüşecekleri için trombositopeniyi düzeltmede etkili olabilecekleri düşünülmektedir.…”
Section: Introductionunclassified